Dietary Antioxidants, Quality of Nutrition and Cardiovascular Characteristics among Omnivores, Flexitarians and Vegetarians in Poland-The Results of Multicenter National Representative Survey WOBASZ - Magdalena Kwaśniewska; Małgorzata Pikala; Oliwia Grygorczuk; Anna Waśkiewicz; Urszula Stepaniak; Andrzej Pająk; Krystyna Kozakiewicz; Paweł Nadrowski; Tomasz Zdrojewski; Aleksandra Puch-Walczak; Andrzej Tykarski; Wojciech Drygas (MDPI AG, 2023)
Several reports have shown that more plant-based dietary patterns provide a higher intake of antioxidants compared to diets rich in meat and animal products. Data on the intake of key nutrients in cardiovascular disease (CVD) prevention in relation to particular diets in countries of Central and Eastern Europe are scarce. The aim of this study was to assess quality of nutrition and CVD characteristics in a representative sample of Polish adults following different dietary patterns. Special regard was paid to the intake of natural antioxidants. The study comprised 13,318 (7159 females) randomly selected adults aged ≥ 20 years participating in the National Multicentre Health Surveys WOBASZ and WOBASZ II. The subjects were categorized into groups of omnivores (92.4%), flexitarians (7.4%) and vegetarians (0.16%) according to type of diet using the Food Frequency Questionnaire and 24 h dietary recall. The obtained results showed that neither flexitarians nor vegetarians represented better dietary habits or lifestyle behaviors compared to omnivores. Flexitarians had significantly lower daily energy intake than omnivores, but their diet was rich in total fat (above 30% of daily energy consumption) and low in fiber. Omnivores declared a higher consumption of fresh vegetables (p < 0.001), fresh fruit (p < 0.01), coffee (p < 0.01) and tea (p < 0.05, in women only) than flexitarians. Omnivores had significantly higher intake of natural antioxidants (vitamin C, E, zinc in both genders and vitamin A in men) as compared with flexitarians. Among women, the highest adherence to the intake of recommended amounts of antioxidant nutrients was noted among omnivores. Among men, vegetarians had the highest proportion of meeting the guidelines for vitamin A (77.8%), E (66.7%) and C (66.7%), while the lowest proportions were found in flexitarians (69.9%, 39.5% and 32.4%, respectively). The groups did not differ in terms of smoking and physical activity level. There were no significant differences in the analyzed CVD characteristics between omnivores and flexitarians. In women, vegetarians had substantially lower BMI than omnivores (p < 0.05) and flexitarians (p < 0.05) and a lower mean serum glucose compared with omnivores (p < 0.01) and flexitarians (p < 0.05). Vegetarians had lower prevalence of hypertension and obesity than meat eaters. In conclusion, the results of the current research showed an inappropriate intake of several nutrients, including highly potent antioxidants, irrespective of the dietary regimen. Flexitarians did not have a more favorable CVD profile than omnivores. Taking into account the growing popularity of diets with reduced animal products, there is a need to elaborate strategies providing Polish adults with guidance regarding properly balanced nutrition.